2021
DOI: 10.1371/journal.pone.0251262
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for inpatient mortality during the first wave of the SARS-CoV-2 pandemic: A retrospective analysis

Abstract: Background The coronavirus disease 2019 (COVID-19) pandemic overwhelmed healthcare systems, highlighting the need to better understand predictors of mortality and the impact of medical interventions. Methods This retrospective cohort study examined data from every patient who tested positive for COVID-19 and was admitted to White Plains Hospital between March 9, 2020, and June 3, 2020. We used binomial logistic regression to analyze data for all patients, and propensity score matching for those treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Hydroxychloroquine oral chemoprophylaxis has been described as effective in young and healthy men in a randomized trial [ 6 ]. Conversely, hydroxychloroquine intake with or without azithromycin has been found to be ineffective against COVID-19 infection in multiple observational [ 7 14 ], intent-to-treat [ 15 ], and randomized controlled [ 16 24 ] studies. Recently published meta-analysis found that hydroxychloroquine had no efficacy as a prophylaxis for COVID-19 infections [ 25 ], and no clinical benefit in patients hospitalized for COVID-19 [ 26 – 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxychloroquine oral chemoprophylaxis has been described as effective in young and healthy men in a randomized trial [ 6 ]. Conversely, hydroxychloroquine intake with or without azithromycin has been found to be ineffective against COVID-19 infection in multiple observational [ 7 14 ], intent-to-treat [ 15 ], and randomized controlled [ 16 24 ] studies. Recently published meta-analysis found that hydroxychloroquine had no efficacy as a prophylaxis for COVID-19 infections [ 25 ], and no clinical benefit in patients hospitalized for COVID-19 [ 26 – 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…While we believe that it was clinically evident which patients indeed required high flow oxygen or some form of non-invasive/invasive ventilation therapy, and therefore did not likely interfere with our results, it is possible that our sample represented a different group of patients compared to that of the general population. Other studies have reported much higher mortality rates during similar study periods [ 45 ], and therefore Aggrenox could have resulted in larger benefits or complications in other patient samples. Lastly, our study predated the introduction of modern vaccines which are now globally available, and therefore it is unclear how Aggrenox may work in patients with previous antibodies, as is for most trials for our study period.…”
Section: Discussionmentioning
confidence: 92%
“…1,2 Our community hospital had a median 22.9% mortality rate among admitted patients between March -June 2020 with a decrease in risk of mortality by 49% each month attributed to the institution's ability to respond dynamically to a novel viral illness. [2][3][4] Debriefs held by the Emergency Department (ED) leadership with interprofessional staff identified systems-based latent safety threats (LST) particularly among newly developed SARS-CoV-2 clinical areas related to infection control precautions, equipment availability, and interdisciplinary team communication. 2 The simulation department at the hospital had a successful history of running quality improvement-based simulation programs 3,[5][6][7] and played a critical role in preparing the hospital during the first wave of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…2 The simulation department at the hospital had a successful history of running quality improvement-based simulation programs 3,[5][6][7] and played a critical role in preparing the hospital during the first wave of the pandemic. 2,3 In June 2020, our hospital leadership provided prediction models to medical staff signaling an anticipated second wave in the early fall. Armed with this knowledge, the hospital's simulation team designed a program with the goal of improving hospital response elicited from concerns that surfaced during department-wide debriefs following the first wave to prepare and manage through the upcoming predicted second wave and beyond.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation